Synthesis of SiO2 nanostructures using sol-gel method - Hassan, Noor Azlina; J.N., Hasnidawani; Hassan, Norita; Surip,, Siti Norasmah (Polish Academy Of Sciences Institute Of Physics, 2016)
Sol-gel method is the simplest method and has the ability to control the particle size and morphology through systematic monitoring of reaction parameters. The objective of this research is to synthesize silica nanostructures by sol-gel method and to characterize the synthesized silica nanostructures. Silica nanoparticles were synthesized via the sol-gel method using Tetraethyl orthosilicate as a precursor. The acetic acid and distilled water were used as the catalyst and the hydrolyzing agent. Varied parameters of the study were the aging time in the range of 2 to 6 h and the calcination temperature in the range of 600–700 ◦C. The obtained silica nanopowder was characterized using FESEM, and Nano-Particle Size Analyzer. The results show that the silica nanospheres were successfully synthesized by using sol-gel method with the optimum parameters of 700 ◦C of calcination temperature and 2 h of aging time. The average size of silica nanoparticles was in the range of 79.68 nm to 87.35 nm.